Corrosive injuries of the upper gastrointestinal tract: A pictorial review of the imaging features - Rohan Kamat; Pankaj Gupta; Yalaka Rami Reddy; Suman Kochhar; Birinder Nagi; Rakesh Kochhar (Indian Journal of Radiology and Imaging, 2019)
Corrosive ingestion is a common form of poisoning. Corrosive agents cause severe damage to the gastrointestinal (GI) tract. The most severe forms of injury can lead to mortality; however, the major concern with this type of injury is life-long morbidity. Upper GI endoscopy is the test of choice for assessing severity in the acute phase of the disease. The long-term management is based on the site, length, number, location, and tightness of the stricture. This information is best provided by the barium contrast studies. In this pictorial review, a spectrum of findings in patients with corrosive injuries of the esophagus and stomach is illustrated. The role of various imaging modalities including barium studies, endoscopic ultrasound, computed tomography, and magnetic resonance imaging is discussed.